2005
DOI: 10.2105/ajph.2004.055319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nativity, Age at Migration, and Acculturation on Smoking Among Adult Houston Residents of Mexican Descent

Abstract: Smoking interventions for people of Mexican descent should be tailored according to gender, nativity, and acculturation level and should target all ages, not just young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
137
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 17 publications
8
137
2
2
Order By: Relevance
“…Mediterranean diet, which would be presumed to be more prevalent among participants born in Greece and Chile but also among participants born in Italy and Yugoslavia, would for instance be a lifestyle factor protecting against both CVD (Bendinelli et al, 2011) and cancer (Couto et al, 2011) mortality. Other studies have documented earlier migrants to be more obese, to have greater levels of cholesterol, to be less physically active and to smoke more cigarettes than those with a shorter duration of residence (Wilkinson et al, 2005;Goel et al, 2004;Gadd et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Mediterranean diet, which would be presumed to be more prevalent among participants born in Greece and Chile but also among participants born in Italy and Yugoslavia, would for instance be a lifestyle factor protecting against both CVD (Bendinelli et al, 2011) and cancer (Couto et al, 2011) mortality. Other studies have documented earlier migrants to be more obese, to have greater levels of cholesterol, to be less physically active and to smoke more cigarettes than those with a shorter duration of residence (Wilkinson et al, 2005;Goel et al, 2004;Gadd et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Age of migration has been widely taken into account in research on cancer epidemiology, in order to disentangle exposure in early life from the influence of the new environment (13,28) . This variable has also been used in studies relating to other diseases (29) or lifestyles (30)(31)(32)(33) . To our knowledge, no study has measured current exposure to socio-cultural norms of the country of origin.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[10][11][12][13] One study, for example, reports that smoking rates are higher among immigrants who have resided in the USA for at least 15 years (12 %) compared to more recent immigrants (5.3 %). 3 There is little agreement regarding why US immigrants increasingly adopt the smoking behaviors of US-born adults over time; however, it has been suggested that (1) this is part of a broader process in which immigrants are exposed and gradually adjust to a new set of US-based customs (acculturation), 5,20 and (2) this is a response to stressors faced in various sociogeographic environments. 7,21 In this article, we focus attention on the second argument and specifically investigate ways in which neighborhood environment may be associated with smoking among adult Brazilian migrants.…”
Section: Introductionmentioning
confidence: 99%